PEMBERDAYAAN USAHA ROTI DAN KERIPIK DI KABUPATEN KARANGANYAR DAN SUKOHARJO MELALUI TEKNOLOGI PENGOLAHAN TEPUNG TERIGU - Irianto, Heru; Haryanto, Budhi; Cahyadin, Malik (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2015)
This activity aims to improve the quality and quantity of production, and to improve the quality of financial management in "Brownis Cinta" and "Salsabila". The method includes the introduction of production equipment, laboratory testing, and training of financial bookkeeping. The conclusion of these activities are: (1) "Brownis Cinta" and "Salsabila" have received and used production equipment to improve the quality and quantity of products;(2) organolopotik test results showed that the age of the product expiry more than three (3) days; and (4) "Brownis Cinta" and "Salsabila" have understood and tried to arrange financial bookkeeping